ПРИНЦИПЫ ПРАВИЛЬНОГО ПИТАНИЯ - Курбанов, Шанияз; Громова, Л.В; Курбанова, Шахноза (MODERN PROBLEMS AND PROSPECTS FOR ORGANIZING A HEALTHY LIFESTYLE AND PROPER NUTRITION, 2024)
ПРИНЦИПЫ ПРАВИЛЬНОГО ПИТАНИЯ